Multimodal real-time imaging with laser speckle contrast and fluorescent contrast - Hyun-Seo Park; Min-Jae Shim; Yikeun Kim; Taek-Yong Ko; Jin-Hyuk Choi; Yeh-Chan Ahn (Photodiagnosis and Photodynamic Therapy)
Introduction: Laser speckle contrast imaging (LSCI) can achieve real-time 2D perfusion maps non-invasively. However, LSCI is still difficult to use in general clinical applications because of movement sensitivity and limitations in blood flow analysis. To overcome this, fluorescence imaging (FI) is combined with LSCI using a light source with a wavelength of 785 nm in near-infrared (NIR) region and validates to visualize real-time blood perfusion. Materials and methods: The system was performed using Intralipid and indocyanine green (ICG) in a flow phantom that has three tubes and controlled the flow rate in 0–150 μl/min range. First, real-time LSCI was monitored and measured the change in speckle contrast by reperfusion. Then, we visualized blood perfusion of a rabbit ear under the non-invasive condition by intravenous injection using a total of five different ICG concentration solutions from 128 μM to 3.22 mM. Results: The combined system achieved the performance of processing laser speckle images at about 37–38 fps, and we simultaneously confirmed the fluorescence of ICG and changes in speckle contrast due to intralipid as a light scatterer. In addition, we obtained real-time contrast variation and fluorescent images occurring in rabbit's blood perfusion. Conclusions: The aim of this study is to provide a real-time diagnostic imaging system that can be used in general clinical applications. LSCI and FI are combined complementary for observing tissue perfusion using a single NIR light source. The combined system could achieve real-time visualization of blood perfusion non-invasively.